Turmeric and Black Cumin essential oil alone and in combination: In vitro and in silico molecular docking studies against inflammation and cancer - Oriola, Ayodeji O.; Kar, Pallab; Singh, Moganavelli; Oyedeji, Adebola O. (Journal of Phytology, 2025)
Hepatocellular carcinoma (HCC) is the fifth most common disease globally. Obesity, long-term hepatitis virus infection, and other factors are among those that lead to the development of HCC, which has a poor survival rate. In Asia and Africa, essential oil-bearing plants like black Cumin and Turmeric are used for various traditional medical purposes. To date, no sufficient information has been provided on the biological properties of the herbal Turmeric-black Cumin combination. To compare the essential oils (EOs) of the Turmeric-black Cumin combined spice with those of the individual ingredients, we looked at in silico molecular docking studies, in vitro anti-inflammatory and anti-cancer characteristics, and the formulation’s potential phytocompounds. The herbal materials were hydro-distilled on a Clevenger apparatus for their essential oils and further characterized using the GC-MS method. In vitro anti-inflammatory activity of the oils was based on the egg albumin denaturation (EAD) assay, while anti-cancer activity was based on the MTT cell viability assay against the HepG2 (human liver cancer cell line) cells. Lastly, the major compounds identified in the extract were molecular docked against the IL-6, TNF-α, and IGF-1R proteins. GC-MS analysis revealed sixty-three major compounds, with ar-Turmerone showing the highest composition in the combined oil (34.45%). The combined oil gave the best anti-inflammatory activity with an IC50 value of 51.33±2.22 μg/mL followed by individual EOs. The result showed that at 100 μg/mL, three tested oils treated RAW 264.7 normal cells exhibited more viability (≥60% growth). In contrast, the combined oil showed the best activity against the HepG2 cell line, which suggests that the combined oil extract is selectively cytotoxic to the cancer cells. The phytochemical alpha-Phellandrene and β-Turmerone showed excellent binding affinity against the three proteins in the in-silico study. As a result of the current research, it appears that combination oil can effectively combat both inflammation and cancer.